A PESTEL and SWOT impact analysis on renewable energy development in Togo - Kansongue, Nanimpo; Njuguna, James; Vertigans, Stephen (Frontiers in Sustainability, 2023)
Similar to most developing countries, Togo continues to rely on the use of traditional forms of biomass energy which causes tremendous socio-economic, environmental, and health hazards. In addition, the imbalanced distribution and use of electricity, petroleum, and liquid gas reflect the disproportion in income and quality of life. This paper plans to highlight the development that renewable energy had in the past decade and the challenges facing the Togolese government, using a framework approach that will best address them. Framework approaches such as PESTEL and SWOT analyses are utilized to access both the internal and external factors in relation to renewable energy development and its impact on Togo. This will provide a better understanding of the sustainability issues facing Togo and provide solutions on the best methods that will lead to greater impact and development. The result shows that renewable energy development in Togo has improved in the past decade and had some impact on socio-economic development. However, better development will be achieved if approaches are introduced to provide a long-term solution to the high capital costs of the technologies, institutional sustainability is incorporated, the number of trained personnel/technical expertise is increased and the Government engagement with funding bodies to secure funds that will favor off-grid and poorest communities is increased. There is also a need to include local participation in the design and operation of projects and introduce a cross-subsidization tariff scheme that covers the operation and maintenance costs of off-grid solar PV users that will favor poor households. Finally, liberalization of the energy sector is needed as well as the government's support to help private investment in rural electrification via Build-Own-Operate arrangements.